Identify Relative importance of covariates in Bayesian lasso quantile regression via new algorithm in statistical program R - Fadel Hamid Hadi Alhusseini; Taha al Shaybawee; Fedaa Abd Almajid Sabbar Alaraje (Revista română de statistică, 2017)
In this paper, we propose a new algorithm to determine the relative importance of covariates by Bayesian Lasso quantile regression for variable selection assigning new formula of Laplace distributions for the regression parameters. Simple and efficient Markov chain Monte Carlo (M.C.M.C) algorithm was introduced for Bayesian sampler. Simulation approaches and two real data set are used to assess the performance of the proposed method. Both simulated and real data sets show that the performs of the proposed method is quite good for Identify Relative importance of covariates.